Pojok Baca “LAPAU” Sebagai Upaya Peningkatan Literasi Inklusi Sosial Masyarakat di Nagari Pariangan Kabupaten Tanah Datar - Afrina, Cut; Irwan, Irwan; Rasyid, Saifuddin; Ardyawin, Iwin; Asisendri, Ingrit (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
This research was aimed to investigate empirically about Pustaka Lapau in increasing reading habits for the community. This research was conducted in Nagari Tuo Pariangan, Tanah Datar Regency, West Sumatera. Pustaka Lapau was operated in this village since 2018 and has been giving the significant contribution to the people in Pariangan. The purpose of this research is to know the impact of the program of Pustaka Lapau. It is also to know the problems in managing reading corner like Pustaka Lapau. Qualitative method was used to conducting this research. Data was collected through interview and observation to the location. After analyzing the data, the researcher finally concluded the finding of this research. First, Pustaka Lapau is one of the solution for increasing reading habits of the people. Second, Pustaka Lapau gives significant contribution to enlarge people knowledge, science, economic and important information. Third, Pustaka Lapau is one of the best strategies for implementing social inclusion in the community.